ChemInform Abstract: Solvent Extraction: The Coordination Chemistry Behind Extractive Metallurgy. Issue 15 (15th April 2014) - Wilson, A. Matthew; Bailey, Phillip J.; Tasker, Peter A.; Turkington, Jennifer R.; Grant, Richard A.; Love, Jason B.
Abstract Review: 49 refs.